خواتین کا حقِ وراثت: ضلع بنوں کے منتخب عدا لتی فیصلوں کے تناظر میں ایک تجزیاتی مطالعہ: Women's Right to Inheritance: An Analytical Study in the light of selected Judicial Decisions of Bannu District (Al-Qamar, 2021)
The Islam is the religion of Allah Almighty and is a complete code of life and all its laws are revealed by Allah. He gave and shared the inheritance with the man and the woman. And let the shares of those who share in the inheritance be clearly stated. Because wealth is attractive thing that a person does not want to leave it. If one does not claim due to social pressure, it is another matter, but the desire and longing to get his right will definitely remain in the heart. in this paper, a research has been done regarding the practical situation of inheritance in the society of Bannu District (a large and famous historical district of Khyber Pakhtunkhwa) in the context of judicial decisions.  Most of the women are deprived from their right of inheritance by their own family members. Male dominant society has manipulated the right, as the women don not claim this in society due to many kind of social, ethical, family pressures. Here we elaborated the divine guidance of inheritance and also highlighted some judicial case in Bannu District.
Keywords: Women right; inheritance of females; law of inheritance in Pakistan; protection of women rights in Pakistan